Pengaruh Penerapan Micro Teaching Terhadap Kompetensi Pedagogik Calon Guru Pendidikan Jasmani - Nada Misva Sebayang; Delima Lena Padang; Totonafo Hulu; Kismiati Lovita Hutasoit; Sandrina Malakiano Naibaho; Tri Yuyanti Sianturi; Rafika Ardilla (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the implementation of micro teaching on the pedagogical competence of prospective physical education teachers. Pedagogical competence is one of the main competencies that must be possessed by prospective teachers, particularly in designing, implementing, and evaluating the learning process effectively. Micro teaching is one of the methods used in teacher education to train teaching skills in a small-scale and controlled setting. This study uses a quantitative approach with an experimental design. The subjects of this study were students of the physical education study program who were taking the micro teaching course. Data were collected through observation, questionnaires, and teaching performance assessments. The data were analyzed using statistical techniques to determine differences in pedagogical competence before and after the implementation of micro teaching. The results of the study indicate that the implementation of micro teaching has a significant effect on improving the pedagogical competence of prospective physical education teachers. Students showed improvement in their ability to plan lessons, manage the classroom, and use appropriate teaching methods and media. Therefore, micro teaching is effective as a means to improve the quality of prospective physical education teachers.